Signs Found on Instagram Account of Discovery Kartika Plaza Hotel - Pramanta, Doni Agung; Warmadewi, Anak Agung Istri Manik; Susini, Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 2 (2024): September, 2024)
This research is titled Signs Found on Instagram Account of Discovery Kartika Plaza Hotel. This thesis aimed to analyze and describe various types of signs and their meanings. The methods used in writing this thesis include data sources, data collection, data analysis, and presentation of analysis results. The data source is gathered from the Instagram stories of the official account @discoverykartikaplaza. Data is collected by observing, capturing screenshots, recording the signs found, and then categorizing the data by type and meaning. The main theory applied to analyze the data is Pierce’s theory of signs as proposed in the book “Semiotics: The Basics Second Edition” by Chandler, with supporting theories that support the main theory proposed by Leech in the book “Semantics: The Study of Meaning, Second Edition.” This study identified 15 signs in the advertisements posted on the @dicoverykartikaplaza Instagram stories, consisting 5 icons, 5 indexes, and 5 symbols. Additionally, several meanings found from seven types of Leech’s theory, namely conceptual meaning, connotative meaning, social meaning, affective meaning, and collocative meaning.